Pemilihan Antibiotik pada Infeksi Kaki Diabetes - Henny Tannady Tan; Ade Dharmawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the International Diabetic Federation (IDF), in 2017, the number of people suffering from DM in Indonesia was 10.3 million people, Indonesia was ranked 6th with the highest number of DM patients. Foot ulcers are often the main cause of hospitalization in DM patients, and DM is the main cause of lower extremity amputation in non-traumatic cases. Currently, Indonesia does not yet have a consensus for the management of diabetic foot infections. Management of diabetic foot infections currently uses guidelines from the Infectious Disease Society of America (IDSA) and the International Working Group of Diabetic Foot (IWGDF) for empirical selection of antibiotics. The basic principles of healing diabetic ulcers are adequate arterial perfusion, proper control of infection, and offloading the ulcer area. Empirical selection of antibiotics often coincides with inadequate information regarding microbiological patterns. Choosing an antibiotic with a spectrum that is too narrow will cause pathogens to be overlooked in infections which are often caused by polymicrobial, and cause clinical deterioration in the patient. Unnecessary selection of broad-spectrum antibiotics can contribute to the increasing problem of antibiotic resistance. Mild and moderate infections can be given antibiotics with a narrower spectrum. Severe infections require parenteral administration to reach therapeutic levels immediately.